مدى انقرائية كتاب " دروس اللغة العربية " الجزء الأول لطلاب الصف الأول في معهد دار السلام كونتور - نافري، أحمد زكي (Kulliyah of Education, International Islamic University Malaysia, 2020)
This research represents a scientific study to evaluate the Dusullughah Al-Arabiyyah textbook by Imam Zarkasyi and Imam Syubani for the first grade of Islamic Teacher Training College at Darussalam Gontor Islamic Institution. The research uses the descriptive and analytical method. It aims to discover the extent of the readability of the Dusullughah Al-Arabiyyah textbook, and to reveal the linguistic characteristics in the book and their relationship with the extent of the readability of the book. The researcher used the Cloze test as an instrument. The researcher found that the result of the test is 75%, and this equals teaching stage or intermediate stage. In addition, given the analysis of the linguistic characteristics of the text, the researcher found that the Dusullughah Al-Arabiyyah textbook is easy and capable of learning by students of the first grade of Islamic Teacher Training College at Darussalam Gontor Islamic Institution. The researcher suggested that the first grade of Islamic Teacher Training College at Darussalam Gontor Islamic Institution continues to teach the Dusullughah Al-Arabiyyah for its suitability as a textbook and appoint an official responsible for assessing the readability of the textbooks at all levels.